Farmers Motivation to Change Land Use and Its Impact on Farmers Income - Nurliani, Nurliani; Saida; Rasyid, Rasmeidah; Rosada, Ida; Asriadi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This research is a survey method of the phenomenon of conversion of cocoa land to corn land in Kebo Village, Lilirilau District, Soppeng Regency, South Sulawesi Province, lasting for 6 (six) months. Data was obtained from observations, interviews using questionnaires. And documentation. The population size is difficult to know, so the Lemeshow formula was used to determine the sample size of 43 farmers. Data analysis uses quantitative descriptive analysis with scoring, analysis of farming income, and analysis of the impact of land conversion. The research results show that pest and disease attacks on cocoa plants provide the highest contribution in motivating farmers to change land use, with an index value of 93.49%. The conversion of cocoa land to corn land has had a positive impact on increasing farmers' income.